Quando os patrões destroem máquinas: o debate em torno das forças produtivas em fábricas recuperadas argentinas e uruguaias - Henrique Tahan Novaes (Ciências Sociais Unisinos)
The article approaches the Socio-Technical Adequation Process in the argentineans and uruguayans Recovered Factories. Facing the fact that a large number of factories failed or were abandoned for their old owners at the end of the century XX and beginning of the century XXI, workers opted to recover their jobs and reestablish production. To achieve our objective - debating the impediments and the possibilities of constructing of the selfmanagement in workers' factories - we introduce the luddish movement and try to demystify some mistaken interpretations. Besides, in Argentina, we have a inside out kind of luddish moviment, since many bosses destroyed machines to block labor control. It was verified that the argentinean and uruguayan innovations tend to the maintenance and enlargement of the industrial knowledge basically, not only of the productive process perspective, but also in some administrative aspects. Many factories opted for the equalitarian partition of the wage. It also can be found small modifications in the machines, in the division of the work and the development of new products. Among the social innovations, we emphasize the creation of spaces for the promotion of cultural events and for the adaptation of the factory to the workers' interests.